Republic of Mozambique : Third Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
Context and policy challenges. Mozambique's macroeconomic performance remains robust, with strong growth and low inflation. In spite of the heightened risks from an uncertain global outlook, growth is expected to be broad-based in the medium term and boosted by the natural resource boom and infrastructure investment. Short-term policy framework. The main short-term challenge is to maintain the growth momentum while preserving fiscal and debt sustainability. The 2014 fiscal stance is expansionary, and fiscal consolidation needs to be initiated in the 2015 budget to restore prudent fiscal management. While low international prices have dampened inflation, the Bank of Mozambique should stay vigilant and adhere to its medium-term inflation target. Key structural reform priorities include improving VAT and overall tax administration, continuing public financial management reforms, strengthening capacity for transparent public investment management and borrowing, and enhancing the business environment and financial sector development. Completion of the LNG contract negotiations is a critical milestone for the launch of this project, one of the largest in sub-Saharan Africa. Medium-term reforms. Fiscal adjustment over the medium term will be essential to preserve debt sustainability and macroeconomic stability. This requires measures to contain current spending pressures while bringing investment to a more sustainable level. Structural reforms focusing on public financial management, monetary policy tools and banking supervision, and business facilitation should be implemented vigorously to sustain growth and render it more inclusive. With foreign aid likely to decline over the medium term, increased borrowing can provide additional resources for improving both Mozambique's physical infrastructure and human capital. To ensure the efficiency of investment and borrowing, further strengthening of investment planning and implementation, and debt management are essential.